The effect of experiences of fairness on honest behavior: a behavioral and neural study - Zhang, Chen; Yin, Ming; Wu, Jixia (Frontiers in Behavioral Neuroscience, 2024)
Prior studies have investigated the relationship between fairness and honesty. However, the differences in the focus of these studies have rendered cross-comparisons between them challenging and of limited value. Thus, this study explored how fairness impacts honest decision-making, focusing specifically on the effect of individuals’ experiences of fairness on their honest behavior. Experiment 1 explored the influence of different experiences of fairness on honest behavior in an altruistic context. In Experiment 2, we measured event-related potentials to further demonstrate the brain mechanisms of these experiences on altruistic dishonest behavior. In Experiment 1, we found that the reaction time for dishonest behavior was shorter for individuals who had positive unfairness experiences with high altruistic objects compared to low altruistic objects. Individuals who had negative unfairness experiences had shorter reaction times when engaging in dishonest behaviors for the sake of high altruistic objects compared to those with equitable experiences. In Experiment 2, in which there was an opportunity to lie for a highly altruistic object, those with fair experiences had greater N2 volatility and smaller P3 volatility than those with positive unfairness experiences. These findings highlight the value of integrating moral psychology and behavioral economics. Discriminant validity across fairness experiences can help illuminate the different motivations behind moral decisions.